PENINGKATAN KETERAMPILAN BERBICARA MENGGUNAKAN METODE SHOW AND TELL PADA SISWA KELAS II SD NEGERI 03 AUR TAJUNGKANG KOTA SAWAHLUNTO - Azahra, Yasha; Adrias; Elfia Sukma; Fikhen Tri Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low speaking skills of second-grade students of SD Negeri 03 Aur Tajungkang, Sawahlunto City. Students still experience difficulties in constructing sentences, choosing vocabulary, speaking fluently, and lack confidence when performing in front of the class. Therefore, a learning method is needed that can train students' courage and speaking skills actively and enjoyably, one of which is through the show and tell method. This study aims to determine the design of teaching modules, implementation, and results of improving students' speaking skills through the application of the show and tell method. This study uses a qualitative and quantitative approach with the type of Classroom Action Research (CAR). This research was conducted in second-grade students of SD N 03 Aur Tajungkang, Sawahlunto City in the second semester of the 2025/2026 academic year with 24 research subjects. The research was conducted in 2 cycles which included the planning, implementation, observation, and reflection stages. Data collection techniques were carried out through interviews, observation, and documentation. The research instruments were observation sheets of teacher and student activities and speaking skills assessment sheets. The results showed that the application of the show and tell method can improve students' speaking skills. Improvements were seen in pronunciation, choice of diction, intonation, fluency, and students' confidence in speaking in front of the class. Students became more active, confident, and able to convey ideas more coherently and clearly. Furthermore, learning activities became more interactive and enjoyable. Based on the research results, it can be concluded that the show and tell method is effective in improving the speaking skills of second-grade students at SD Negeri 03 Aur Tajungkang in Sawahlunto City in learning Indonesian.